Design, Synthesis and Self‐Assembly of Functional Amphiphilic Metallodendrimers. Issue 1 (8th January 2020) - Neranon, Kitjanit; Alberch, Laura; Ramström, Olof
Abstract: A new family of alkynylated, amphiphilic dendrimers consisting of amidoamine linkers connected to 5, 5′‐functionalized 2, 2′‐bipyridine cores has been developed and evaluated in the formation of metallodendrimers of different generations and in self‐assembly protocols. A convergent synthetic strategy was applied to provide dumbbell‐shaped amphiphilic dendrimers, where the 2, 2′‐bipyridine cores could be coordinated to Fe II centers to afford corresponding metallodendrimers. The ability of the metallic‐ and non‐metallic dendritic structures to self‐assemble into functional supramolecular aggregates were furthermore evaluated in aqueous solution. Spherical aggregates with sizes of a few hundred nanometers were generally produced, where controlled disassembly of the metallodendrimers through decomplexation could be achieved. Abstract : In control ! A new family of amphiphilic dendrimers have been used to form metallodendrimers. The dendritic structures self‐assemble into functional, spherical supramolecular aggregates in aqueous solution. Controlled assembly/disassembly of the metallodendrimers through complexation could be achieved.